Labor Market Concentration and Stayers' Wages: Evidence from France - Andrea Bassanini; Cyprien Batut; Eve Caroli (Institute of Labor Economics (IZA), 2021)
We investigate the impact of labor market concentration on stayers' wages, where stayers are defined as individuals who were already employed in the same firm the year before. Using administrative data for France, we show that the elasticity of stayers' wages to labor market concentration ranges between -0.0185 and -0.0230, depending on the instrument we use, and controlling for labor productivity and local product market concentration. This represents between about two thirds and three fourth of the elasticity we estimate for new hires. Given the strong wage rigidities characterizing the French labor market, this estimate can be considered a lower bound of the effect of labor market concentration on stayers' wages in an international perspective.
Keywords: J31; J42; L41; 330; labor market concentration; monopsony; wages; stayers